Do Crises Hit Female-Managed and Male-Managed Firms Differently? Evidence from the 2008 Financial Crisis - Ahmed, Tanima; Muzi, Silvia; Ueda, Kohei (World Bank, Washington, DC, 2020)
While efforts are currently in place to collect data on the economic consequences of the COVID-19 pandemic, this note looks at the experience of the 2008 financial crisis to gain insights on possible differential effects of crises on female and male entrepreneurs. Specially, the note uses firm-level data collected immediately after the 2008 financial crisis in six countries in Eastern Europe and Central Asia (Bulgaria, Hungary, Latvia, Lithuania, Romania, and Turkey) to look at two aspects of the differential effect of the crisis. First, whether there is a difference in the exit rate for firms with male vs. female top managers; and second, whether, among firms that stayed in business, female-managed firms are affected disproportionally. Results show that firms run by female top managers are more likely to exit the market. Secondly, when able to stay in business, male and female-managed firms suffered a similar impact in the short term; however, female-managed firms suffered more than male-managed firms in the longer term.